Effectiveness of Simulation Based Learning on Clinical Skills Competence among Undergraduate Nursing Students - Ahmed, Zeeshan; Hussain, Altaf; Badil,; Murtaza, Ghulam; Perdhoomun,; Manzoor, Zeeshan; Memon, Rubina (Indus Journal of Bioscience Research, 2025)
Objective: To evaluate the enhancement of clinical skills competence in undergraduate nursing students through the implementation of simulation‐based learning (SBL) to bridge the gap between theoretical knowledge and clinical practice. Methods: A quasi‐experimental, single-group pre–post assessment study was conducted. Eighty students were selected by non-probability convenience sampling. Written consent was obtained, and a pre-assessment was carried out using a head-to-toe assessment checklist. The intervention involved visualizing a video and a demonstration of the head-to-toe assessment skill in class using scenario-based methods. A post-assessment was performed using the same checklist. Data were analyzed using SPSS version 26. Results: There was a significant improvement in skills after the intervention. The overall mean score increased from 6.35 ± 2.41 before the intervention to 14.43 ± 2.75 after the intervention (p < 0.0001), as measured by a paired t-test. Conclusion: The study demonstrated that SBL significantly enhances clinical skills competence among undergraduate nursing students. The findings support the adoption of SBL as an effective teaching methodology that leads to considerable improvement in clinical performance.